Differential biomarker responses and associated health risks in two pelagic fish species from the Mediterranean Sea, Egypt - Amel H. El-Gendy; Hala Ahmed Abdel-Mohsen; Md. Mushfiqur Rahman; Abdullah Alkahtane; Sulaiman Alharbi; Saleh A. Alfarraj; Mansour Almansour; Milton Wainwright; Md. Habibullah-Al-Mamun; Abdullah Aleidan (Marine Pollution Bulletin, 2026)

Risk-informed flood management under climate variability: A hybrid temporal–ensemble artificial intelligence framework - Md Mehedi Hassan Melon; Md Zia Uddin Raihan; S. M. Ahad Maruf; Md. Nahid Hasan; Md. Habibullah Biswas; Hasan Ahamed Alif; Md. Jisan Mashrafi; Mezabahnur Masum (Bulletin of Atmospheric Science and Technology, 2026)

Factors Affecting Agricultural Productivity Among Potato Farmers in Baghlan Province - Hafizullah Radmand; Habibullah Rezaei; Ali Keramatzadeh; Farshid Eshraghi (American Journal of Potato Research, 2026)

Climate change and water security in Afghanistan: a comprehensive review - Zabihullah Karokhil; Habibullah Salim; Najibullah Totakhil (Arabian Journal of Geosciences, 2026)

Mechanistic Insights into Mercury Tolerance and Detoxification in the Potential Hyperaccumulator Fern Pteris vittata - Hongye Wan; Xiaoli Qian; Guangle Qiu; Ming Ao; Le Wang; Longchao Liang; Jialiang Han; Md. Habibullah-Al-Mamun; Jinjuan Li; Pan Wu; Shouyang He; Xiaohang Xu (Journal of Hazardous Materials, 2026)

Nyctanthes arbor-tristis attenuates hyperglycemia: an integrated experimental and computational investigation - Brij Raj Singh; Jagat Pal Yadav; Ashish R. Dwivedi; Ankit Kumar Singh; Vikas Kumar; Habibullah Khalilullah; Prateek Pathak; Amita Verma (DARU Journal of Pharmaceutical Sciences, 2026)

Surrounding Rock Deformation Mechanisms and Control in Deep Mining: A Comprehensive Review - Md Habibullah; Deyu Qian; Arifuggaman Arif; Md Owalid Hossen; Samina Islam; Md Zahedul Islam (Geotechnical and Geological Engineering, 2026)

Recent trends in anti-Alzheimer’s potential of novel biologically active isatin analogues: synthetic strategies, structural activity relationship studies and molecular docking insights - Rajarshi Nath; Anhic Chakraborty; Md. Jawaid Akhtar; Indrajit Maity; Swastika Ganguly; Bhupender Nehra; Sumel Ashique; Shah Alam Khan; Mohd Tariq; Soumyadeep Bakshi; Biplab Debnath; Sabina Yasmin; et al. (Molecular Diversity, 2026)

Marine invertebrates as ecological integrators of microplastic pollution: Trait-based evidence from coastal Bangladesh - Swachsa Rahman; Saikat Das; Abdullah Yebna Ahammad; Arnob Ghosh; Md. Mushfiqur Rahman; Md. Biplob Hasan; Mahmudul Hasan; Goutam Kumar Kundu; Mir Shariful Islam; Md. Habibullah-Al-Mamun (Regional Studies in Marine Science, 2026)

Designing landslide mitigation strategies through developing knowledge aware deep learning model integrated explainable artificial intelligence - Inzamam Ul Haq; Habibullah; Shafiq Ahmed; Swapan Talukdar; Mansoor Ahmad; Md Sarfaraz Asgher; Imran Khan; G.V. Ramana (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Mechanistic insights into multi-metal toxicity interactions via plasmid DNA assay - Le Wang; Yushuang Yang; Jinjuan Li; Xiaohang Xu; Md. Habibullah-Al-Mamun; Yongqiang Yuan (Journal of Trace Elements in Medicine and Biology, 2026)

Phosphorus availability modulates OsPTF1 expression in Oryza sativa L. - Muhammad Saeed Ahmad; Zulfiqar Ali; Rizwana Maqbool; Sultan Habibullah Khan (Cereal Research Communications, 2026)

Comparative Assessment of Toxic Heavy Metals Contamination in Farmed and Wild Fish in Bangladesh, and Implications for Human Health - Nahida Akter; Udoy Das; Mahima Ranjan Acharjee; Md. Mushfiqur Rahman; Arnob Ghosh; Helena Khatoon; Md. Hasan Faruque; Md. Habibullah-Al-Mamun (Biological Trace Element Research, 2026)

Species-specific bioaccumulation of toxic metals in coastal seaweeds from the northeast Bay of Bengal: Implications for human health risk - Md. Biplob Hasan; Md. Mushfiqur Rahman; Arnob Ghosh; Swachsa Rahman; Mahmudul Hasan; Md. Habibullah-Al-Mamun; Mir Shariful Islam (Regional Studies in Marine Science, 2026)

Elevated mercury accumulation and inefficient biomagnification in subterranean streams: Insights from karst cave ecosystems - Chan Li; Weifeng Du; Mengyi Chen; Kang Luo; Chengxiang Xu; Xiaohang Xu; Md. Habibullah-Al-Mamun; Lisha Lei; Longchao Liang; Guangle Qiu (Journal of Hazardous Materials, 2026)

Advancements and Challenges in Biogas Technology: A Comprehensive Review on Sustainable Approach to Waste Management and Renewable Energy - Manasa P; Kruthi Doriya; Paramjeet Saroj; Saranya Gunasekaran; Manupati Hemalatha; Sk Habibullah; Sarada Prasanna Mallick (BioEnergy Research, 2025)

Comparative assessment of nutritional quality and ecotoxicological biomarkers in Paphia textile clams from the coastal areas in Egypt - Amel H. El-Gendy; Md. Mushfiqur Rahman; Arnob Ghosh; Mir Shariful Islam; Abdullah A. Alkahtane; Saleh Al Farraj; Md. Habibullah-Al-Mamun (Regional Studies in Marine Science, 2025)

Development of a fipronil insecticide response spectrum model for juvenile Chinook salmon (Oncorhynchus tshawytscha) - Kara E. Huff Hartz; Katie J. Knaub; Louise Cominassi; Giovanni S. Molinari; Shane Power; Mia Arkles; S.D.M. Chinthaka; Andrea Chandler; Md. Habibullah-Al-Mamun; Gregory Whitledge; Amelie Segarra; Richard E. Connon; et al. (Environmental Pollution, 2025)

Correction: Radon levels and its geostatistical distribution in dwellings of Kabul Afghanistan - Kamal Hadad; Habibullah Sharifi; Mohammad-Nabi Karimi; Ataollah Rabiee (Environmental Geochemistry and Health, 2025)

Mining-Induced Subsidence Predicting and Monitoring: A Comprehensive Review of Methods and Technologies - Arifuggaman Arif; Chunlei Zhang; Mingjie Feng; Mahabub Hasan Sajib; Md Habibullah; Sobuj Hasan; Md Sohel Rana; Khezr Mohammadamini; Mohammed Alip; Ye Zhang (Geotechnical and Geological Engineering, 2025)

Structural and functional insights into Jasmonate ZIM-domain 2 (GhJAZ2) interactions in cotton fiber development via Jasmonic acid signaling - Muhammad Sulyman Saleem; Sultan Habibullah Khan; Zunaira Afzal Naveed (Plant Gene, 2025)

Radon levels and its geostatistical distribution in dwellings of Kabul Afghanistan - Kamal Hadad; Habibullah Sharifi; Mohammad-Nabi Karimi; Ataollah Rabiee (Environmental Geochemistry and Health, 2025)

Corrigendum to “Bioaccumulation variability and human health risk assessment of organochlorine pesticides in edible fish and shellfish from the Northeast Bay of Bengal” [Mar. Pollut. Bull. 215 (2025) 117856] - Md. Habibullah-Al-Mamun; Sadman Sakib; Rupesh Das; Md. Hasan Faruque; Amel H. El-Gendy; Mansour I. Almansour; Saleh Alfarraj (Marine Pollution Bulletin, 2025)

Integrated groundwater quality assessment using GIS and statistical analysis techniques at Islamkot subdistrict in the Thar desert area - Imran Aziz Tunio; Sheeraz Ahmed Memon; Love Kumar; Habibullah Abbasi; Habib Ursani; Sher Muhammad Ghoto (Groundwater for Sustainable Development, 2025)

Bioaccumulation variability and human health risk assessment of organochlorine pesticides in edible fish and shellfish from the Northeast Bay of Bengal - Md. Habibullah-Al-Mamun; Sadman Sakib; Rupesh Das; Md. Hasan Faruque; Amel H. El-Gendy; Mansour I. Almansour; Saleh Alfarraj (Marine Pollution Bulletin, 2025)

Trace Metal Pollution near a Coal-Fired Power Plant in Bangladesh: Implications for Environmental and Human Health - Anondo Kumar Ray; Md. Hasan Faruque; Rupesh Das; Sadman Sakib; Mohammad Moniruzzaman; Md. Aftab Ali Shaikh; Anwar Hossain; Md. Habibullah-Al-Mamun (Water, Air, & Soil Pollution, 2025)

Analysing Technical, Pure Technical, Scale, and Economic Efficiency: A Case Study of Potato Producers in Khinjan District - Hafizullah Radmand; Habibullah Rezaei; Ramtin Joolaie (Potato Research, 2025)

Design and Development of Ketoconazole Loaded Nanoemulgel for the Improved Topical Therapy of Onychomycosis Using Chemical Penetration Enhancers - Yashwant Giri; Amulyaratna Behera; Biswaranjan Mohanty; Sk Habibullah; Pradyumna Kumar Dixit; Gurudutta Pattnaik; B. Jyotirmayee (Journal of Pharmaceutical Innovation, 2025)

Development of a response spectrum model for bifenthrin in juvenile Chinook Salmon (Oncorhynchus tshawytscha) - Katie Knaub; Md Habibullah-Al-Mamun; Kara E. Huff Hartz; Gregory Whitledge; Louise Cominassi; Andrea Chandler; Mia Arkles; John Reeve; Amelie Segarra; Richard E. Connon; Michael J. Lydy (Environmental Pollution, 2025)

Harnessing psychological dynamics to enhance climate-smart agricultural practices: a comparative study of small-scale farmers in China and Pakistan - Ghulam Raza Sargani; Habibullah Magsi; Lili Yao; Junhu Ruan (Environment, Development and Sustainability, 2025)

Occurrence of trace elements in water, fish and shellfish from estuarine and coastal areas of the east coast of Bangladesh, northeast Bay of Bengal: Human health risk implications - Seema Rani; Md. Kawser Ahmed; Chen Keliang; Kazi Belayet Hossain; Abu Hena Md. Yusuf; K.M. Azam Chowdhury; Md. Habibullah-Al-Mamun; Makidul Islam Khan; Nor Aida Mahiddin; Zulhilmi Ismail; Md. Saiful Islam (Marine Pollution Bulletin, 2025)

Developing a method to estimate aerosol generation during poultry slaughtering and defeathering in Bangladesh: An experimental study - Nadia Ali Rimi; Md. Habibullah Fahad; Andrew Clark; Rebeca Sultana; Kamal Hossain; Md. Khaled Saifullah; Ireen Sultana Shanta; David E. Swayne; Md. Zakiul Hassan; Syed Mohammad Golam Mortaza; Sayeda Tasnuva Swarna; Md. Giasuddin; et al. (Building and Environment, 2025)

Rock Slope Stability Prediction: A Review of Machine Learning Techniques - Arifuggaman Arif; Chunlei Zhang; Mahabub Hasan Sajib; Md Nasir Uddin; Md Habibullah; Ruimin Feng; Mingjie Feng; Md Saifur Rahman; Ye Zhang (Geotechnical and Geological Engineering, 2025)

Air stability enhancement and mechanism of Mg-Ca-hydride-based hydrolysis materials - Qin Huang; Ruijun Qian; Bingshou Gong; Habibullah; Ji Zhou; Xue Yao; Yao Wang; Yigang Yan; Yungui Chen; Chaoling Wu (Chemical Engineering Journal, 2025)

Geochemical evolution, geostatistical mapping and machine learning predictive modeling of groundwater fluoride: a case study of western Balochistan, Quetta - Taimoor Shah Durrani; Malik Muhammad Akhtar; Kaleem U. Kakar; Muhammad Najam Khan; Faiz Muhammad; Maqbool khan; H. Habibullah; Changaiz Khan (Environmental Geochemistry and Health, 2025)

Development of intensity–duration–frequency curves for Herat, Afghanistan: enhancing flood risk management and implications for infrastructure and safety - Ziaul Haq Doost; Shakhawat Chowdhury; Ahmed M. Al‑Areeq; Ibrahim Tabash; Guled Hassan; Habibullah Rahnaward; Abdul Raqib Qaderi (Natural Hazards, 2024)

Correction to: Environmental and human health risk of potentially toxic metals in freshwater and brackish water Nile tilapia (Oreochromis niloticus) aquaculture - Md. Shafiujjaman; Shankar Chandra Mandal; Mohammad Moniruzzaman; Md. Habibullah-Al-Mamun; Md. Aftab Ali Shaikh; Kozo Watanabe; Anwar Hossain (Environmental Geochemistry and Health, 2024)

Environmental and human health risk of potentially toxic metals in freshwater and brackish water Nile tilapia (Oreochromis niloticus) aquaculture - Md. Shafiujjaman; Shankar Chandra Mandal; Mohammad Moniruzzaman; Md. Habibullah-Al-Mamun; Md. Aftab Ali Shaikh; Kozo Watanabe; Anwar Hossain (Environmental Geochemistry and Health, 2024)

Deciphering the catalytic activity of nickel anchored on Fe3O4@SiO2@3-CPMS@L as a magnetically recoverable nanocatalyst for the efficacious reduction of 4-nitrophenol, nitrobenzene, and methyl orange - Iftkhar Ahmad; Hani Alothaid; Mahmoud M. Habibullah; Tahir Hussain Wani; Saiqa Ikram (Journal of Environmental Management, 2024)

Recent progress in carbonaceous materials for the hydrogen cycle: Electrolytic water splitting, hydrogen storage and fuel cells - Guanghui Xia; Habibullah; Qingfeng Xie; Qin Huang; Meitong Ye; Bingshou Gong; Rui Du; Yao Wang; Yigang Yan; Yungui Chen; Chaoling Wu (Chemical Engineering Journal, 2024)

Exploring nut quality traits in almond varieties: a comparative study of local and foreign cultivars and their F1 hybrid offsprings - Hatice Özcan; Müjgan Güney; Harun Karcı; Habibullah Tevfik; Salih Kafkas; İzzet Acar; Ebru Kafkas (Euphytica, 2024)
Almonds are one of the most popular and widely consumed tree nuts in the world, prized for their taste, texture, and nutritional benefits. However, the quality and characteristics of almonds can vary significantly depending on the variety and growing conditions. In this context, a comparative study was conducted to explore the nut quality traits of almond local and foreign cultivars, as well as their F1 hybrid offspring resulting from crossbreeding. “Nut quality” is a dynamic concept changing based on consumer needs and perceptions that reflect sociocultural evolution. The aim of this study was to identify the most promising almond varieties and hybrids based on some nut quality traits including macro–micro elements and tocopherol contents. To accomplish this goal, samples were collected from local (Gulcan 2 and Nurlu) and foreign (Lauranne and Guara) almond cultivars, as well as F1 hybrid offspring resulting in two cross-breading (“Gulcan 2 × Lauranne” and “Guara × Nurlu”), and conducted a comprehensive analysis using high-performance liquid chromatography and atomic absorption spectroscopy. Our results showed that the nut quality traits of almonds can vary significantly among different cultivars and hybrids, with some varieties and hybrids exhibiting superior characteristics compared to others. These findings provide important insights into the potential for improving almond quality through crossbreeding and the development of new varieties with improved characteristics which can help inform breeding programs and improve the quality of almonds available in the market.

Using an internal body residue approach to assess acute pesticide toxicity in juvenile Chinook salmon (Oncorhynchus tshawytscha) - Kara E. Huff Hartz; Katie J. Knaub; Md. Habibullah-Al-Mamun; Richard E. Connon; Greg W. Whitledge; Amélie Segarra; Michael J. Lydy (Environmental Pollution, 2024)

Maximizing microgrid resilience: A two-stage AI-Enhanced system with an integrated backup system using a novel hybrid optimization algorithm - M.H. Elkholy; Mahmoud Elymany; Soichiro Ueda; Issoufou Tahirou Halidou; Habibullah Fedayi; Tomonobu Senjyu (Journal of Cleaner Production, 2024)

Construction of a high-density genetic linkage map and QTL analysis using an interspecific F1 population in pistachio - Md Rashedul Islam; Habibullah Tevfik; Hayat Topçu; Harun Karcı; Salih Kafkas (Tree Genetics & Genomes, 2023)

Construction of high density linkage maps in almond and synteny analysis with peach, Japanese apricot and sweet cherry genomes - Habibullah Tevfik; Harun Karcı; Jennifer Wai; Salih Kafkas (Euphytica, 2023)

Buckwheat (Fagopyrum esculentum): its impact on wireworm development and survival - Christine Noronha; Suqi Liu; Md. Habibullah Bahar; Natasha Mosher-Gallant (Arthropod-Plant Interactions, 2023)
Buckwheat ( Fagopyrum esculentum ) is a member of the Polygonaceae family, cultivated as a cover crop to suppress or reduce weeds and improve soil health. In our field studies, buckwheat gave significant potato tuber protection from wireworm damage after two consecutive years of cropping. In this study, we identified the mechanism underlying the beneficial effect of buckwheat on wireworm suppression. Results show high wireworm numbers in buckwheat than other host plants in bioassays conducted under greenhouse and field conditions which reject the hypothesis that buckwheat has antifeedant activity. We found that newly hatched neonate wireworms feeding on either barley or buckwheat plants for 120 days, showed reduced body weight and head capsule size. The larvae feeding on buckwheat were 60% and 30% smaller than the ones feeding on barley. Survival was also impacted with 44% of the neonate larvae surviving on barley plants, and only 15% when feeding on buckwheat roots over 120 days. A similar bioassay with small to medium-sized wireworms showed higher mortality, lower weight gain and smaller head capsule size. Wireworms feeding on buckwheat were deformed and demonstrated irregular growth. In conclusion, this study revealed that buckwheat did not repel wireworms and they chose to feed on the roots despite it not being a good host. Long-term feeding on buckwheat roots caused reduced weight gain, abnormal growth, and reduced survival. This study provided a better understanding of how buckwheat functions as a biopesticide for wireworm control and its potential for use in an IPM program.

The changing landscape of agriculture: role of precision breeding in developing smart crops - Amna Chaudhry; Ahtsham Ul Hassan; Sultan Habibullah Khan; Asim Abbasi; Aiman Hina; Muhammad Tajammal Khan; Nader R. Abdelsalam (Functional & Integrative Genomics, 2023)

Occurrence of Organochlorine Pesticides (OCPs) Residues in Farmed and Wild Fish in Bangladesh and Implications for Human Health - Md. Habibullah-Al-Mamun; Sanjida Akter Tanima; Bijoya Paul; Md. Al Zahid; Md. Humayun Kabir; Shamim Ahmed; Shankar Chandra Mandal; Anwar Hossain (Exposure and Health, 2023)

Bioplastics from waste biomass of marine and poultry industries - Amna Arif; Farrukh Azeem; Ijaz Rasul; Muhammad Hussnain Siddique; Muhammad Zubair; Faizan Muneer; Warda Zaheer; Habibullah Nadeem (Journal of Biosciences, 2023)

Marine Heatwaves in the Indonesian Fisheries Management Areas - Ahmad Dhuha Habibullah; Ayi Tarya; Nining Sari Ningsih; Mutiara Rachmat Putri (Journal of Marine Science and Engineering, 2023)
Ocean temperatures increased during the 20th century and are predicted to continue to rise during the 21st century. Simultaneously, the extreme phenomena of shorter time ocean warming, known as Marine Heatwaves (MHWs), are also taking place. The present study used the Daily Optimum Interpolation Sea Surface Temperature (DOISST) v2.1 with a spatial resolution of 0.25˚. The time period of the DOISST data used in this study was from January 1, 1982 to December 31, 2020, and the region was 90° E–150° E and 16° S–16° N, which is divided into 11 Fishing Management Areas (FMAs). MHWs have a set of metrics derived from the SST data to describe the statistical characteristics of each event. To examine and quantify the influence of the Pacific Ocean and the Indian Ocean, we used the Niño 3.4 SST index and the Dipole Mode Index (DMI), respectively. Based on the data analysis, there has been an increase in the duration and frequency of the occurrence of MHWs in the study area, with the highest increase occurring in FMA 573, FMA 716, and FMA 711. Based on the severity, MHWs in Indonesia are dominated by category I, which is dominantly located in FMA 716, category II in FMA 573, category III with the center of events in FMA 771, and category IV with irregular spatial patterns.

Research trends in biodiversity loss: a bibliometric analysis - Yan-Ling Tan; Thian-Hee Yiew; Muzafar Shah Habibullah; Jen-Eem Chen; Siti Nuur-Ila Mat Kamal; Nur Adilah Saud (Environmental Science and Pollution Research, 2023)

Customization of GIS for spatial and temporal analyses of Air Quality Index trends in Kabul city - Fazal Rahman Afghan; Habibullah Habib; Noor Ahmad Akhunzada; Wafaurahman Wafa; Mohammad Dawod Shirzad; Kawoon Sahak; Sayed Kazem Hashimi; Mujeebullah Mujeeb; Karima Wardak; Mujib Rahman Ahmadzai (Modeling Earth Systems and Environment, 2022)

Habitat change and biodiversity loss in South and Southeast Asian countries - Yan-Ling Tan; Jen-Eem Chen; Thian-Hee Yiew; Muzafar Shah Habibullah (Environmental Science and Pollution Research, 2022)

Toxic Effects of Arsenic in Commercially Important Fish Rohu Carp, Labeo rohita of Bangladesh - Md. Golam Rabbane; Md. Alamgir Kabir; Md. Habibullah-Al-Mamun; Md. Ghulam Mustafa (Fishes, 2022)
This study was designed to elucidate the effects of arsenic (As) on the morpho-behavior, growth development and molecular mechanisms of a commercially important fish, rohu carp, Labeo rohita, in Bangladesh. Fish fry with an average weight of 387.5 ± 169.25 mg and an average length of 3.35 ± 0.37 cm were collected from a local hatchery in Mymensingh, Bangladesh and acclimatized for a week in the Department of Fisheries, University of Dhaka before starting the exposure with arsenic. Fishes were exposed for a period of 14 days with three treatments of NaAsO2, namely treatment 1(T1)—2.5 mg/L; treatment 2 (T2)—15 mg/L; and treatment 3 (T3)—30 mg/L, along with a control (C)—0.0 mg/L, with three replicates. These concentrations were determined based on the LC50 value for 96 h measured for this experiment. This study revealed remarkable morphological abnormalities and deformities in arsenic-exposed rohu carp. In fish exposed to 30 mg/L, caudal fin erosion was a frequent deformity. There was no significant difference in RNA:DNA ratio among the treatments. The overall weight of fish was decreased as the concentration of arsenic was increased. The T3 fish had a statistically significant negative weight gain (−0.05 ± 0.07 g), but the other treatments (T1 and T2) and control fish had no significant weight gain. Different types of histopathological changes were observed in the gills and intestines of arsenic-treated fish. Necrosis and severe damages were found in the secondary lamellae of gills at the highest arsenic concentration (30 mg/L). Epithelial lifting, irregular shape and damages in the gill raker were also observed in the primary lamellae of the gills for the same treatment. In this study, the expression of heat shock protein (HSP 60) and metallothionein (MT) genes was assessed by qPCR, and these genes were upregulated in different treatments compared to controls. The findings of the present study suggest that arsenic pollution significantly changes the morphology, behavior, growth, development, histopathology and molecular mechanisms of this economically important fish, rohu carp, in Bangladesh.

Genetic dissection of grain yield traits in a large collection of spring wheat (Triticum aestivum L.) germplasm - Sultan Habibullah Khan; Muhammad Sajjad; Saima Gulnaz; Sundas Waqar; Munawar Shahzad; Saima Mir Arain (Journal of Crop Science and Biotechnology, 2022)

Trace metals and organochlorine pesticide residues in imported fishes in Bangladesh and human health risk implications - Md. Monirul Islam; Nusrat Jahan Avha; Shamim Ahmed; Md. Ahedul Akbor; Md. Sofiqul Islam; Farhana Mostafiz; Md. Habibullah-Al-Mamun (Environmental Science and Pollution Research, 2022)

Characterization of new COBRA like (COBL) genes in wheat (Triticum aestivum) and their expression analysis under drought stress - Muhammad Zaheer; Shoaib Ur Rehman; Sultan Habibullah Khan; Shahmeer Shahid; Awais Rasheed; Rabia Naz; Muhammad Sajjad (Molecular Biology Reports, 2022)

Antibiotics, antibiotic-resistant bacteria, and resistance genes in aquaculture: risks, current concern, and future thinking - Anwar Hossain; Md. Habibullah-Al-Mamun; Ichiro Nagano; Shigeki Masunaga; Daisuke Kitazawa; Hiroyuki Matsuda (Environmental Science and Pollution Research, 2022)

Financial inclusion-environmental degradation nexus in OIC countries: new evidence from environmental Kuznets curve using DCCE approach - Imran Sharif Chaudhry; Zulkornain Yusop; Muzafar Shah Habibullah (Environmental Science and Pollution Research, 2022)

Impact of climate change on biodiversity loss: global evidence - Muzafar Shah Habibullah; Badariah Haji Din; Siow-Hooi Tan; Hasan Zahid (Environmental Science and Pollution Research, 2022)

Isolation and identification of low-density polyethylene degrading novel bacterial strains - Habibullah Nadeem; Khush Bakhat Alia; Faizan Muneer; Ijaz Rasul; Muhammad Hussnain Siddique; Farrukh Azeem; Muhammad Zubair (Archives of Microbiology, 2021)

Accumulation of Trace Metals in Indigenous Fish Species from the Old Brahmaputra River in Bangladesh and Human Health Risk Implications - Sabikunnahar Shorna; Saika Shawkat; Anwar Hossain; Shamshad B. Quraishi; A. K. M. Atique Ullah; Mohammad Mozammal Hosen; Md. Kamal Hossain; Badhan Saha; Bijoya Paul; Md. Habibullah-Al-Mamun (Biological Trace Element Research, 2021)

Comparative toxicity of transgenic cotton CEM-33, Bt-906 varieties, and Annona squamosa L., seed extract against biotic potential of Spodoptera litura (Fab.) - Qurban Ali Arain; Muhammad Farhanullah Khan; Habibullah Rana; Amjad Sultan; Zubair Ahmed; Hakim Ali Sahito; Muhammad Asif Farooq; Muhammad Faheem Akbar; Tasneem Kousar (International Journal of Tropical Insect Science, 2021)

Comparative efficacy of biogenic zinc oxide nanoparticles synthesized by Pseudochrobactrum sp. C5 and chemically synthesized zinc oxide nanoparticles for catalytic degradation of dyes and wastewater treatment - Khadija Siddique; Muhammad Shahid; Tanvir Shahzad; Faisal Mahmood; Habibullah Nadeem; Muhammad Saif ur Rehman; Sabir Hussain; Omer Sadak; Sundaram Gunasekaran; Tahseen Kamal; Ikram Ahmad (Environmental Science and Pollution Research, 2021)

Towards connecting carbon emissions with asymmetric changes in economic growth: evidence from linear and nonlinear ARDL approaches - Amdadullah Baloch; Said Zamin Shah; Muzafar Shah Habibullah; Balach Rasheed (Environmental Science and Pollution Research, 2021)

Identification of Edible Fish Species of Pakistan Through DNA Barcoding - Muhammad Zubair Ghouri; Muhammad Ismail; Muhammad Asif Javed; Sultan Habibullah Khan; Nayla Munawar; Abdullah Bin Umar; Mehr-un-Nisa; Syed Ovais Aftab; Shazia Amin; Zulqurnain Khan; Aftab Ahmad (Frontiers in Marine Science, 2020)

Concentration and isotopic composition of mercury in a blackwater river affected by extreme flooding events - Martin Tsz‐Ki Tsui; Habibullah Uzun; Alexander Ruecker; Hamed Majidzadeh; Yener Ulus; Hongyuan Zhang; Shaowu Bao; Joel D. Blum; Tanju Karanfil; Alex T. Chow (Limnology and Oceanography, 2020)
Torrential rain and extreme flooding caused by Atlantic hurricanes mobilize a large pool of organic matter (OM) from coastal forested watersheds in the southeastern United States. However, the mobilization of toxic metals such as mercury (Hg) that are associated with this vast pool of OM are rarely measured. This study aims to assess the variations of total Hg (THg) and methylmercury (MeHg) levels and the isotopic compositions of Hg in a blackwater river (Waccamaw River, SC, U.S.A.) during two recent extreme flooding events induced by Hurricane Joaquin (October 2015) and Hurricane Matthew (October 2016). We show that extreme flooding considerably increased filtered THg and MeHg concentrations associated with aromatic dissolved organic matter. During a 2‐month sampling window each year (October–November), we estimate that about 27% (2015) and 78% (2016) of the average amount of Hg deposited atmospherically during these 2 months was exported via the river. The isotopic composition of Hg in the river waters was changed only slightly by the substantial inputs of runoff from surrounding landscapes, in which mass‐dependent fractionation (as δ 202 Hg) decreased from −1.47 to −1.67‰ and mass‐independent fractionation (as ∆ 199 Hg) decreased from −0.15 to −0.37‰. The slight variations in Hg isotopic composition during such extreme flooding events imply that sources of Hg in the river are nearly unchanged even under the very high wet deposition of Hg derived from the intensive rainfall. The majority of Hg exported by the river (74–85%) is estimated to have been derived from dry deposition to the watersheds. An increase in frequency and intensity of Atlantic hurricanes is expected in the next few decades due to further warming of ocean surface waters. We predict that increased hurricanes will mobilize more dry‐deposited Hg and in situ produced MeHg from these coastal watersheds where MeHg can be extensively bioaccumulated and biomagnified in the downstream aquatic food webs.

Microbial l-asparaginase: purification, characterization and applications - Faizan Muneer; Muhammad Hussnain Siddique; Farrukh Azeem; Ijaz Rasul; Saima Muzammil; Muhammad Zubair; Muhammad Afzal; Habibullah Nadeem (Archives of Microbiology, 2020)

Bioaccumulation of trace metals in freshwater prawn, Macrobrachium rosenbergii from farmed and wild sources and human health risk assessment in Bangladesh - Farhana Mostafiz; Md Monirul Islam; Badhan Saha; Md. Kamal Hossain; Mohammad Moniruzzaman; Md. Habibullah-Al-Mamun (Environmental Science and Pollution Research, 2020)

Examining the effects of climate change on rice production: case study of Pakistan - Abbas Ali CHANDIO; Habibullah MAGSI; Ilhan OZTURK (Environmental Science and Pollution Research, 2020)

Effects of allelic variation at Rht-B1 and Rht-D1 on grain yield and agronomic traits of southern US soft red winter wheat - Habibullah Hayat; R. Esten Mason; Dennis N. Lozada; Andrea Acuna; Amanda Holder; Dylan Larkin; Zachary Winn; Jamison Murray; J. Paul Murphy; David E. Moon; Randal G. Miller (Euphytica, 2019)

Distribution of polycyclic aromatic hydrocarbons (PAHs) in commonly consumed seafood from coastal areas of Bangladesh and associated human health implications - Md. Habibullah-Al-Mamun; Md. Kawser Ahmed; Md. Saiful Islam; Masahiro Tokumura; Shigeki Masunaga (Environmental Geochemistry and Health, 2019)

Distribution, Source Apportionment, and Risk Assessment of Polycyclic Aromatic Hydrocarbons (PAHs) in the Surficial Sediments from the Coastal Areas of Bangladesh - Md. Habibullah-Al-Mamun; Md. Kawser Ahmed; Anwar Hossain; Shigeki Masunaga (Archives of Environmental Contamination and Toxicology, 2019)

Polychlorinated biphenyls (PCBs) in commonly consumed seafood from the coastal area of Bangladesh: occurrence, distribution, and human health implications - Md. Habibullah-Al-Mamun; Md. Kawser Ahmed; Md. Saiful Islam; Anwar Hossain; Masahiro Tokumura; Shigeki Masunaga (Environmental Science and Pollution Research, 2019)

Genome-Wide Analysis of Potassium Transport-Related Genes in Chickpea (Cicer arietinum L.) and Their Role in Abiotic Stress Responses - Farrukh Azeem; Bilal Ahmad; Rana Muhammad Atif; Muhammad Amjad Ali; Habibullah Nadeem; Sabir Hussain; Hamid Manzoor; Muhammad Azeem; Muhammad Afzal (Plant Molecular Biology Reporter, 2018)

Arsenic in the food chain and assessment of population health risks in Bangladesh - Md. Saiful Islam; Md. Kawser Ahmed; Md. Habibullah-Al-Mamun; Dennis Wayne Eaton (Environment Systems and Decisions, 2017)

Financial development and sectoral CO2 emissions in Malaysia - Ibrahim Kabiru Maji; Muzafar Shah Habibullah; Mohd Yusof Saari (Environmental Science and Pollution Research, 2017)

Use of TALEs and TALEN Technology for Genetic Improvement of Plants - Zulqurnain Khan; Sultan Habibullah Khan; Muhammad Salman Mubarik; Bushra Sadia; Aftab Ahmad (Plant Molecular Biology Reporter, 2017)

Organophosphate flame retardants in the indoor air and dust in cars in Japan - Masahiro Tokumura; Rurika Hatayama; Kouichi Tatsu; Toshiyuki Naito; Tetsuya Takeda; Mohammad Raknuzzaman; Md. Habibullah -Al-Mamun; Shigeki Masunaga (Environmental Monitoring and Assessment, 2017)

Trace metal contamination in commercial fish and crustaceans collected from coastal area of Bangladesh and health risk assessment - Mohammad Raknuzzaman; Md Kawser Ahmed; Md Saiful Islam; Md Habibullah-Al-Mamun; Masahiro Tokumura; Makoto Sekine; Shigeki Masunaga (Environmental Science and Pollution Research, 2016)

Health risk assessment due to heavy metal exposure from commonly consumed fish and vegetables - Md. Saiful Islam; Md. Kawser Ahmed; Md. Habibullah-Al-Mamun; Mohammad Raknuzzaman; Mir Mohammad Ali; Dennis Wayne Eaton (Environment Systems and Decisions, 2016)

Use of RSM modeling for optimizing decolorization of simulated textile wastewater by Pseudomonas aeruginosa strain ZM130 capable of simultaneous removal of reactive dyes and hexavalent chromium - Zahid Maqbool; Sabir Hussain; Tanvir Ahmad; Habibullah Nadeem; Muhammad Imran; Azeem Khalid; Muhammad Abid; Fabrice Martin-Laurent (Environmental Science and Pollution Research, 2016)

Health risk assessment of trace elements via dietary intake of ‘non-piscine protein source’ foodstuffs (meat, milk and egg) in Bangladesh - Nazma Shaheen; Md. Kawser Ahmed; Md. Saiful Islam; Md. Habibullah-Al-Mamun; Avonti Basak Tukun; Saiful Islam; Abu Torab M.A. Rahim (Environmental Science and Pollution Research, 2016)

Apportionment of heavy metals in soil and vegetables and associated health risks assessment - Md. Saiful Islam; Md. Kawser Ahmed; Md. Habibullah-Al-Mamun (Stochastic Environmental Research and Risk Assessment, 2016)

Human health risk assessment of heavy metals in tropical fish and shellfish collected from the river Buriganga, Bangladesh - Md. Kawser Ahmed; Mohammad Abdul Baki; Md. Saiful Islam; Goutam Kumar Kundu; Md. Habibullah-Al-Mamun; Santosh Kumar Sarkar; Md. Muzammel Hossain (Environmental Science and Pollution Research, 2015)

Trace elements in different land use soils of Bangladesh and potential ecological risk - Md. Saiful Islam; Md. Kawser Ahmed; Md. Habibullah-Al-Mamun; Mohammad Raknuzzaman (Environmental Monitoring and Assessment, 2015)

Trace elements in two staple cereals (rice and wheat) and associated health risk implications in Bangladesh - Md. Kawser Ahmed; Nazma Shaheen; Md. Saiful Islam; Md. Habibullah-Al-Mamun; Saiful Islam; Cadi Parvin Banu (Environmental Monitoring and Assessment, 2015)

Metal speciation in soil and health risk due to vegetables consumption in Bangladesh - Md. Saiful Islam; Md. Kawser Ahmed; Md. Habibullah-Al-Mamun (Environmental Monitoring and Assessment, 2015)

Simple, efficient, and improved synthesis of Biginelli-type compounds of curcumin as anticancer agents - Ramdayal Sharma; Surender Singh Jadav; Sabina Yasmin; Sandeep Bhatia; Habibullah Khalilullah; Mohamed Jawed Ahsan (Medicinal Chemistry Research, 2015)

Metal Speciation in Sediment and Their Bioaccumulation in Fish Species of Three Urban Rivers in Bangladesh - Md Saiful Islam; Md Kawser Ahmed; Mohammad Raknuzzaman; Md Habibullah-Al-Mamun; Shigeki Masunaga (Archives of Environmental Contamination and Toxicology, 2015)

Arsenic and lead in foods: a potential threat to human health in Bangladesh - Md Saiful Islam; Md Kawser Ahmed; Md Habibullah-Al-Mamun; Kazi Nazrul Islam; Md Ibrahim; Shigeki Masunaga (Food Additives & Contaminants: Part A, 2014)

Trace metals in soil and vegetables and associated health risk assessment - Md Saiful Islam; Md Kawser Ahmed; Md Habibullah-Al-Mamun; Shigeki Masunaga (Environmental Monitoring and Assessment, 2014)

Synthesis and anticonvulsant evaluation of 2-(substituted benzylidene/ethylidene)-N-(substituted phenyl)hydrazinecarboxamide analogues - Mohamed Jawed Ahsan; Habibullah Khalilullah; Sabina Yasmin; Surender Singh Jadav; James P. Stables; Jeyabalan Govindasamy (Medicinal Chemistry Research, 2013)

The Effect of Substrate, Season, and Agroecological Zone on Mycoflora and Aflatoxin Contamination of Poultry Feed from Khyber Pakhtunkhwa, Pakistan - Sahib Alam; Hamid Ullah Shah; Habibullah Khan; Naresh Magan (Mycopathologia, 2012)

The low down on association mapping in hexaploid wheat (Triticum aestivum L.) - Muhammad Sajjad; Sultan Habibullah Khan; Abdul Mujeeb Kazi (Journal of Crop Science and Biotechnology, 2012)

Synthesis of some new 3,4-dihydro-2H-1,3-benzoxazines under microwave irradiation in solvent-free conditions and their biological activity - Mymoona Akhter; Shaikh Habibullah; Syed Misbahul Hasan; Mohammad Mumtaz Alam; N. Akhter; Mohammad Shaquiquzzaman (Medicinal Chemistry Research, 2011)

Relevance of Helicobacter pylori genotypes in gastric pathology and its association with plasma malondialdehyde and nitric oxide levels - Santosh K. Tiwari; G. Manoj; Vishwas Sharma; G. Sivaram; R. Saikant; Avinash Bardia; Varun K. Sharma; Zakia Abid; Aleem A. Khan; M. Aejaz Habeeb; C. M. Habibullah; B. Santhosh Kumar; et al. (Inflammopharmacology, 2010)

Effect of ultraviolet B (302 nm) irradiation on viability, metabolic and detoxification functions of goat hepatocytes – in vitro study - Naseem Begum Shakeel; Vijayalakshmi Venkateshan; Parveen; Adarsh K. Capoor; Mohammed Aejaz Habeeb; Ansar Ali Khan; Syed Muzeeb; N. V. S. Rao Mamidi; Aleem Ahmed Khan; Chittoor Mohammed Habibullah (Molecular and Cellular Biochemistry, 2005)

Differential responses of UV-B irradiation on the viability and intracellular calcium influx in goat hepatocytes–in vitro effect - Vijayalakshmi Venkateshan; Naseem Begum Shakeel; Nalam Madhusudhan Rao; Vijayalakshmi Amash; Nandini Rangarajan; Chittoor Mohammed Habibullah (Molecular and Cellular Biochemistry, 2004)

UV-B Induced stimulation of phosphatidylinositol 3-kinase in human fetal hepatocytes - V. B. Chari; R. S. R. Gaddameedi; M. Raghuveer Singh; Sathish Kasina; Khaja Khaleel Ur. Rahman; C. M. Habibullah; Surya S. Singh (Indian Journal of Clinical Biochemistry, 2004)

Agrotis segetum granulosis virus as a control agent against field populations ofAgrotis ipsilon andA. Segetum [Lep.: Noctuidae] on tobacco, okra, potato and sugar beet in northern pakistan - O. Zethner; Bashir M. Khan; M. Ismail Chaudhry; B. Bolet; Sharfuddin Khan; Habibullah Khan; Hanif Gul; L. Øgaard; M. Zaman; Gul Nawaz (BioControl, 1987)